Language, Music, and Computing : First International Workshop, LMAC 2015, St. Petersburg, Russia, April 20-22, 2015, Revised Selected Papers - Eismont, Polina; Konstantinova, Natalia; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the proceedings of the First International Workshop on Language, Music and Computing, LMAC 2015, held in St. Petersburg, Russia, in April 2015. The 13 papers presented in this volume were carefully reviewed and selected from 38 submissions. They were organized in topical sections on music and language in education; corpus studies of language and music; problems of notation; and linguistic studies of music. .
Keywords: Information systems; Natural language processing (Computer science).; Artificial intelligence; Music; Performing arts; Computer Appl. in Arts and Humanities; Natural Language Processing (NLP).; Artificial Intelligence; Music; Performing Arts; Information Systems and Communication Service